Five-years retrospective study on utilization and uptake pattern of family planning services in primary health centres in a peri-urban settlement in southwest Nigeria - Afolabi, Esther K.; Oyebamiji, Suliyat O.; Oyinlola, Funmilola F.; Ani, Odinaka B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Family planning is one of the most basic and essential healthcare services that can promote and ensure women's reproductive health worldwide. However, there has been a low level of utilisation of family planning services by women in developing countries. Therefore, the paper documented the utilisation rate, the uptake pattern of family planning services, and the socio-demographic characteristics of the women who attended the selected primary health centres in the Ife-Central local government area. Method: A five-year retrospective review of primary health centre’s records of clients who attended selected health centres from January 2017-December 2021. Data was obtained from the client cards and the family planning record book. A total of 2572 clients’ records were evaluated. Results: the study revealed the modal age group of 25-34 (58%) and modal parity of 3-4 (51%) children. The most significant proportion of the women was married (94.6%), with a secondary level of education (89%). Injectables were the most utilized family planning services among women in primary health centres, followed by the uptake of condoms. The Implant was the only increasing uptake pattern of family planning services within 5 years in primary health centres. Conclusion: Injectable contraceptives have a higher utilization rate, and the uptake pattern of family planning services varied in selected PHCs. However, the uptake pattern of implants increased consistently. Therefore, there is a need for continuous awareness creation and advocacy for the uptake of family planning services to promote women’s health and well-being. Trial registration: It was not retrospectively registered.